Satellite -telemetry and mass communication based early warning system for human-elephant coexistence in Southern India’s agroforestry landscapes - Muliya, Sanath K.; Kolipakam, Vishnupriya; Pandey, Ramesh K.; Sharma, Souritra; Pushkar, Kumar; Kuttappa, Thammaiah C.; Manjunath, Chethan C.; Bindhani, Uddalak T.; Kawlni, Lallianpuii; Tiwari, Virendra R.; Qureshi, Qamar (Frontiers in Conservation Science, 2026)
Elephants, vital to India’s ecological and cultural fabric, now navigate increasingly fragmented habitats, rising incidence of negative interactions with humans. This has resulted in substantial casualties on both sides, with India reporting over 500 human deaths and approximately 100 elephant fatalities from retaliatory killings annually. Long-term solutions to mitigate human-elephant conflict include enhancing habitat quality and connectivity, restoring historic migratory routes, and protecting existing elephant corridors while establishing new ones where necessary. However, implementing such extensive habitat modifications presents significant challenges due to complex political, societal, and economic factors. This necessitates interim measures to manage conflicts within tolerable levels until comprehensive long-term solutions can be achieved. Here, we reflect upon a sustainable coexistence case study by leveraging technological advancements in satellite telemetry and mass communication within a landscape that supports the single largest population of Asian elephants globally. This integrated strategy combines adaptive management with active engagement of affected local communities, who collaborate with rapid response teams and wildlife managers to monitor and respond to elephant movements, ensuring that conservation efforts are locally grounded and socially acceptable. Such an approach offers potential to ensure the long-term persistence of this flagship species while balancing ecological and human needs.